From Lawmen to Plowmen : Anglo-Saxon Legal Tradition and the School of Langland - Yeager, Stephen M., 1979- (Book collections on Project MUSE., 2014)
By comparing Anglo-Saxon charters, sermons, and law codes with Langland's Piers Plowman and similar poems, Yeager demonstrates that this legal and homiletical literature had an influential afterlife in the fourteenth-century poetry of William Langland and his imitators.